The Association of Tissue transglutaminase antibody titer with duodenal histological changes in children with celiac disease in Tishreen Hospital 2018-2019 - ابراهيم علي; حجوز عقيل; درويش محمد (Latakia University Journal -Medical Sciences Series, 2021)
Background: Celiac disease (CD) is one of the most common autoimmune digestive disorders in children which prevelance has recently increased in our society. Objective: This study aims to assess the correlation between the titers of tissue anti-transglutaminase IgA (anti-tTG-IgA) antibodies and the degree of histologic changes in duodenal biopsy in children with celiac disease who admitted to Tishreen University Hospital in Lattakia during the period between (2018-2019). Materials and Methods: A cross-sectional analytic study was conducted on 50 children who admitted to the paediatrics department at Tishreen University Hospital in Lattakia during the period from April 2018 to March 2019 and were diagnosed with celiac disease by performing an esophagogastroduodenoscopy and taking biopsies from the duodenum and studying the degree of histologic changes. According to the March classification results, a serological titration was performed for their transglutaminase (anti tTG - IgA) antibodies,and serological titration of Total IgA was performed for their negative t transglutaminase antibodies to dectect IgA deficiency . Results : The study sample included 50 children with celiac disease , with an average age of 8 years and slight preference for females. Growth failure was the most common clinical manifestations in children with 38% prevelance, followed by chronic diarrhea by 18%. The sensitivity of tissue transglutaminase antibodies ( anti-tTG-IgA) in diagnosing celiac disease reached 94%, and it was found that the value of anti tTG-IgA antibody increased with age and with increased histological changes degree of duodenal biopsies. Conclusions: This study showed that growth failure is the most common clinical symptom of celiac disease, followed by chronic diarrhea and abdominal pain. It also confirmed the high sensitivity of transglutaminase antibodies in the diagnosis of celiac disease, and showed that the value of anti tTG-IgA antibody increased with increasing histological change degree of duodenal biopsies and with age.